Testing of empirical grounds for theoretical models of real exchange rate: research of real exchange rate between RSD and Euro - Petrović, Predrag (Industrija, 2013)
The focus of this research holds the most important determinants of real exchange rate covered by various theoretical models. The empirical testing was carried out on the real exchange rate between RSD and Euro for the period from January 2007 to December 2010, which was significantly imposed by availability of consistent time series. The research pertains to five basic model specifications and is based on the testing of time series cointegration by applying Johansen and Engle-Granger’s test. The obtained results have shown that the observed models do not have grounds in empirical data. Time series figuring in models are not cointegrated, and besides that, the estimated cointegration coefficients have signs opposite to the expected ones in large number of cases. In our opinion, the reasons for such findings can be found in the fact that used time series are quite short, i.e. they pertain to the period of only four years, as well as that prices of some significant services are still under the administrative control. Still, despite the aforementioned lacks, we think that our findings can be accepted as preliminary knowledge about the ability of the observed models to explain the dynamics of real exchange rate between RSD and Euro.